Prehabilitation is effective in relieving pain after knee arthroplasty, but has little effect on length of stay and knee function: a meta-analysis of randomized controlled trials - Zhang, Weishuai; Lu, Xuchao; Yang, Nannan; Zhu, Xianyou; Hu, Haotian (Frontiers in Medicine, 2025)
PurposeThe efficacy of preoperative rehabilitation (prehabilitation) for patients undergoing knee arthroplasty remains controversial. Prehabilitation is defined as the implementation of functional exercises, health education, and preemptive medication before surgery to improve postoperative outcomes, typically compared to conventional care protocols. Existing studies have reported inconsistent results regarding its benefits. This meta-analysis aims to evaluate the impact of prehabilitation on hospital length of stay, postoperative pain, and knee function in patients undergoing knee arthroplasty.MethodsPubMed, Cochrane, Embase, and Web of Science were searched from their establishment to 16 January 2024. An additional 19 articles were obtained by reading the relevant literature or by a reference search. All clinical randomized controlled trials (RCTs) related to the prehabilitation of total knee arthroplasty were included. All trials were analyzed by two independent reviewers, and the resulting data were analyzed using a random effects model and processed using Review Manager5.4 statistical software. The main outcome measures are as follows: visual analog scale(VAS), knee flexion and extension, and length of stay (LOS).ResultsA total of 18 articles, encompassing 21 RCTs with 2,150 participants (1,167 in the prehabilitation group and 983 in the control group), were included. The analysis revealed that prehabilitation significantly reduced postoperative pain at 1, 3, and 6 months, as evidenced by lower VAS scores. Improvements in knee function were noted in terms of knee extension at 1 month and knee flexion at 3 months postoperatively. However, no significant difference was observed in the length of hospital stay.ConclusionPrehabilitation before knee arthroplasty effectively alleviates postoperative pain and partially enhances knee function in the early postoperative period but does not significantly affect the length of hospital stay.